An investigation of the dose-dependent safety of bemiparin sodium: A cell culture study - Emre Kubat; Ozer Aylin Gurpinar; Tuna Demirkiran (Turkish Journal of Vascular Surgery)
Aim: Fibroblasts are common cells in subcutaneous tissue and they have an important role on healing process. Although patients who are receiving first-generation low molecular weight heparins are more likely to experience skin responses, there is no study evaluating the effect of bemiparin sodium on subcutaneous fibroblasts following administration. In the present study, we aimed to evaluate the effects of bemiparin sodium on fibroblast cell viability in cell culture model. Material and Methods: The L929 cells were incubated for 12 hours in 96-well culture dishes. Fresh medium containing different concentrations of bemiparin was added in five different concentrations (Dilution I: 3,500 IU; Dilution II: 1,750 IU; Dilution III: 875 IU; Dilution IV: 437.5 IU; Dilution V: 218.75 IU). A control group was established with drug-free culture medium. Cell viability analysis was performed after 48 hours of incubation by the standard 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) method. The change in cell morphology was examined at each dilution by direct and acridine orange/propidium iodide staining. Results: The highest cytotoxic effect was observed in dilution I compared to the control group (p [Turk J Vasc Surg 2024; 33(2.000): 59-63]